Pengaruh Inovasi Menu Produk Pastry dan Layanan Breakfast terhadap Kepuasan Tamu di Hotel Indigo Seminyak Bali - I Gede Agustin Anggara Putra; Desak Made Purnama Dewi; I Ketut Sutapa (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2026)
This study analyzes the effect of pastry menu innovation and breakfast service on guest satisfaction at Hotel Indigo Seminyak Bali. The increasing competition in the hospitality industry requires hotels to continuously improve service quality and guest experience. Menu innovation and breakfast service are key factors that directly influence guest satisfaction, particularly through the overall dining experience during guests’ stay. This research used a quantitative descriptive approach with data collected through questionnaires, observation, and documentation from 120 respondents selected using purposive sampling. The data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, t-test, and F-test with SPSS version 26. The results show that menu innovation has a positive and significant effect on guest satisfaction (p < 0.05). Breakfast service also has a positive and significant effect on guest satisfaction (p < 0.05). Simultaneously, both variables significantly influence guest satisfaction (F = 41.701). Among the two variables, breakfast service is the most dominant factor affecting guest satisfaction. These findings indicate that improving menu innovation and breakfast service can enhance guest satisfaction and strengthen competitiveness in the hospitality industry.